PENGARUH KOMPETENSI PROFESIONAL DAN PEDAGOGIK TERHADAP KINERJA GURU AKUNTANSI PADA MADRASAH ALIYAH NEGERI DI KOTA PALU - Latif, Zulkefi M.A. (Katalogis, 2017)
Mastery of teacher competence is a set of capabilities that must mark the teacher in order to realize their performance appropriately and effectively. Competence in this case that the professional and pedagogical influence on teacher performance. In this study aimed to analyze the effects of both the professional competence of teachers and pedagogical competence of teachers on teacher performance at MAN in the city of Palu. To analyze the quantitative, descriptive analysis was used, which outlines the respondent's age, gender, Â the length of service and class as well as the competence of teachers affect the performance guru. Whereasto determine the effect of independent variables on the dependent variable, Â the namely quantitative analysis used multiple linear regression analysis. The independent variable of professional competence and pedagogical teacher jointly significant effect on the performance of teachers in Madrasah Aliyah in Palu. Partially professional competence variables significantly influence the performance of teachers in Madrasah Aliyah in Palu, while the pedagogical competence not significant effect on the performance of teachers in Madrasah Aliyah in Palu. The results of the regression coefficient (b) indicate that the independent variable professional competence of the dominant influence on the performance of teachers in Madrasah Aliyah in Kota Palu.Â